The management of cystic fibrosis chronic rhinosinusitis: An evidenced‐based review with recommendations. Issue 9 (10th January 2022) - Spielman, Daniel B.; Beswick, Daniel M.; Kimple, Adam J.; Senior, Brent A.; Aanaes, Kasper; Woodworth, Bradford A.; Schlosser, Rodney J.; Lee, Stella; Cho, Do‐Yeon; Adappa, Nithin D.; DiMango, Emily; Gudis, David A.
Abstract : Background: Cystic fibrosis (CF) chronic rhinosinusitis (CRS) has emerged as a distinct diagnostic entity, unique from other endotypes of CRS in its presentation, pathophysiology, diagnosis, treatment, and outcomes. As the sinonasal health of this patient population may have broad effects on pulmonary health and quality of life, a comprehensive understanding of the diagnostic and therapeutic approach to CF CRS is essential. In recognizing recent scientific advances and unique treatment modalities specific to this challenging patient population, in this review we systematically evaluate the scientific literature and provide an evidenced‐based review with recommendations (EBRR) for fundamental management principles of CF CRS. Methods: A systematic review of the literature was performed. Studies evaluating interventions for the management of CF CRS were included. An iterative review process was implemented in accordance with EBRR guidelines. A treatment recommendation was generated based on an assessment of the benefits, harms, and the overall grade of evidence. Results: We evaluated the published literature on 5 unique topics. Each of the following therapeutic categories was investigated explicitly for treatment outcomes in patients with CF CRS: (1) nasal saline; (2) intranasal corticosteroids (INCS); (3) topical antibiotics; (4) cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapy; and (5) endoscopic sinus surgery (ESS). Conclusion: Based on the currently available evidence, nasal saline, ESS, and CFTR modulators are recommended in the management of CF CRS when appropriate. INCS and topical antibiotics are options . Clinical judgment and experience are essential in caring for patients with this uniquely challenging disorder.